Analisis Kualitas Laporan Keuangan pada Sekretariat Komisi Pemilihan Umum Provinsi Sumatera Utara - Lili Puteri Handayani; Oktarini Khamilah Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the Accountability of the General Election Commission Secretariat of North Sumatra Province in compiling financial reports. qualitative approach. Research using a qualitative approach emphasizes the analysis of inductive thinking processes related to the dynamics of relationships between observed phenomena, and always uses scientific logic. Observation of the concept of accountability, this study focuses on finding weaknesses or deficiencies in the implementation of financial management. This study took the KPU of North Sumatra Province as the research area. With a focus on the implementation of financial management in the implementation of the 2019 Election. The main reason for this research is that since the establishment of this institution as an Election Organizer, even though the KPU has succeeded in holding the Election, in terms of financial management the KPU has not yet received an Unqualified Opinion (WTP) from the BPK. So the researcher feels that it is necessary to look for the causes of not going well with accountability at the KPU office of North Sumatra Province through this scientific research. This scientific research is carried out based on conceptual studies and through analysis using scientific research methods that can be scientifically justified and effective. So based on this assumption, researchers are interested in conducting research with the title analysis of the quality of financial reports at the General Elections Commission secretariat of North Sumatra Province.